Pengaruh Pemberdayaan dan Pendistribusian Zakat Konsumtif Terhadap Kesejahteraan Mustahiq Pada Program Sukabumi Sehat BAZNAS Kab Sukabumi - awaliyah, hasna (COMPETITIVE, 2023)
ABSTRACTThis study aims to explain the effect of empowerment and distribution on the welfare of mustahiq. The variables used in this study are Empowerment (X1), Distributing (X2), Welfare Mustahiq (X3). This research was conducted at BAZNAS Sukabumi Regency. Sources of data used are primary data sources obtained by means of questionnaires and structured interviews. The data analysis used is validity and reliability test and classical assumption test and hypothesis test. The benefits in this research are expected to enrich the repertoire of knowledge, especially in empowering and distributing zakat. the results of the research on the variable X1 to Y 0.000 <0.05 and the t-count value 4.058 > 1.984 and the research results from the X2 variable to Y 0.000 <0.05 and the t-count value 10.068 > 1.984 and the results of the X1 variable research and X2 results to the Y variable is 0.000 < 0.05 and f count 51.093 > f table value 3.09.Keywords: Empowerment, Distribution, Welfare Mustahiq.